Development of a master of science, nursing and interprofessional leadership program: AACN essentials in action. - Antonelli, Mary T.; Poza, Ricardo; Richards, Rachel; Vitello, Joan (Journal of Professional Nursing, 2024)
Leadership acumen, interprofessional relationships, and knowledge of healthcare operations are essential proficiencies for nurses to navigate the dynamic and complex healthcare landscape. The American Association of Colleges of Nursing (AACN) re-envisioned the academic nursing standards, The Essentials: Core Competencies for Professional Nursing Education (Essentials), to guide curricular development in preparing nurses with the aptitude to meet these challenges. The purpose of this project was to develop an innovative Master of Science nursing program to address the challenges facing the RN workforce. A relationship-based framework and the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model were used to guide the development of the program using the Essentials to inform curricular design. A Nursing and Interprofessional Leadership Master of Science program was designed comprising seven core courses with two tracks, Bachelor of Nursing and Post Graduate Option. The program was created during the COVID-19 pandemic, which may have influenced the data used for the program's design. Healthcare complexities are requiring nursing education to evaluate curricula for advanced knowledge and skills. A Nursing and Interprofessional Leadership Master of Science degree program guided by the Essentials was developed to meet this challenge. • Nursing education is entering a transformative era. • Master of Science Interprofessional Leadership specialty nursing program was created. • The American Association of Colleges of Nursing's revised Essentials guided the process.